RISK FACTORS OF UTERINE SCAR DYSPLASIA DEVELOPMENT AFTER CAESAREAN SECTION ASPECTS AND TERMINOLOGY (World Bulletin of Public Health, 2023)
The aim of the review was to summarise information and terminological analysis of the English- and Russian-language literature devoted to the assessment of uterine scar condition after caesarean section, as well as to identify the terms that are most appropriate for use outside and during pregnancy, in labour and in the postpartum period.